Facile Synthesis of 3D Graphene Flowers for Ultrasensitive and Highly Reversible Gas Sensing. (14th September 2016) - Wu, Jin; Feng, Shuanglong; Wei, Xingzhan; Shen, Jun; Lu, Wenqiang; Shi, Haofei; Tao, Kai; Lu, Shirong; Sun, Tai; Yu, Leyong; Du, Chunlei; Miao, Jianmin; et al.
Abstract : Fabrication of nanostructured graphene (Gr) for gas sensing applications has become increasingly attractive. For the first time, 3D graphene flowers (GF) cluster patterns are grown directly on an Ni foam substrate by inexpensive homebuilt microwave plasma‐enhanced chemical vapor deposition (MPCVD) using the gas mixture H2 /C2 H4 O2 @Ar as a precursor. The interim morphologies of the synthesized GF are investigated and the growth mechanism of the GF film is proposed. The GF are decomposed to few‐layer Gr sheets by ultrasonication in ethanol. For the first time, MPCVD‐synthesized Gr is exploited to fabricate a gas sensor that exhibits an ultrahigh sensitivity of 133.2 ppm −1 to NO2 . Outstanding sensor responses of 1411% and 101% to 10 ppm and 200 ppb NO2, respectively, are achieved. Furthermore, a low theoretical detection limit of 785 ppt NO2 is achieved. An ultrafast (within 2 s) recovery is observed at room temperature, and an imbedded microheater is employed to improve the selectivity of NO2 detection relative to humidity. This work represents a simple, clean, and efficient route to synthesize large‐area cauliflower Gr for gas detection with high performance, including ultrahigh sensitivity, good selectivity, fast recovery, and reversibility. Abstract : 3D graphene flower (GF) structures are synthesized successfully by exploiting facile microwave plasma‐enhanced chemical vapor deposition. The GF growth mechanism is revealed. The synthesized GF are employed to detect NO2 gas with ultrahigh sensitivity (133.2 ppm −1 ), good selectivity, reversibility, and ultrafast recovery. The high sensing performance is attributed to the porous structures, abundant oxygenated functional groups, and defects.